Contrastive Analysis of Javanese and Japanese Speech Levels as a Form of Politeness Learning Among the Younger Generation - Rahadini, Astiana Ajeng; Pribadi, Nirbito Hanggoro; Wijayanti, Kenfitria Diah; Kurwidaria, Favorita; Said, Dewi Pangestu; Veronika, Prima (Sutasoma : Jurnal Sastra Jawa, 2025)
The purpose of our research is: (1) to provide and add references related to the contrastive levels of speech in Javanese and Japanese, (2) to explain the differences in the levels of speech in Javanese and Japanese, (3) to introduce politeness to the younger generation through the use of good and correct language. The research method we used was a literature study by prioritizing the results of the analysis of a reference as a reference for the writing data from the research we conducted. The results of the study show that: 1) Javanese and Japanese both have levels of speech in their use as daily communication tools as a form and parameter of politeness. 2) Javanese recognizes the level of speech in Javanese which is divided into four language varieties, namely, Ngoko lugu (Nl), Ngoko alus (Na), Krama lugu (Kl) and Krama alus (Ka). The level of speech in Japanese is classified into three parts and is used by considering the age or social strata of the interlocutor, how close or familiar the speaker is with the interlocutor, and paying attention to Uchi and Soto. Keego is divided into three parts, namely, Sonkeego (Sk), Kenjoogo (Kj), Teeneego (Tn). 3) Speech levels are introduced and passed down through examples of everyday life and through learning.